Redesigning Passenger Distribution System of KRL Commuter Line: An Integrative Approach - Ho, Hwi-Chie; Venessa, Venessa; Sopha, Bertha Maya (Yayasan Riset dan Pengembangan Intelektual (YRPI), 2025)
Commuter line electric rail (KRL) has become a critical mode of public transportation supporting urban mobility in densely populated areas. However, the rapid growth of urban populations and the corresponding increase in daily commuters have created significant challenges in delivering optimal and comfortable services due to overcrowding. This study addresses these challenges by enhancing passenger comfort on KRL commuter lines through the redesign of the passenger distribution system considering personal space along with passenger flow management. An integrative approach combining ergonomic approach in determining carriage capacity, passenger flow management, and simulation-based analysis was employed. Empirical data were collected through observation, empirical survey, and direct anthropometric measurement. Observations on passenger density were conducted on the Cikarang line during peak morning hours, focusing on mixed-gender carriages. Anthropometric measurements involving 238 subjects alongside carriage dimensions were analyzed to determine the capacity of carriage using ergonomic principles of personal space The results revealed that the carriage capacity of 150 passengers balancing comfort and efficiency. An innovative passenger distribution system deploying queuing system equipped with integrated sensors providing real-time number of passengers and innovative automatic door-closing mechanism at the carriages were proposed and tested under current passenger density and determined carriage capacity using discrete-event simulation implemented in Arena software. This study provides novel contribution both practically and theoretically demonstrating the application of ergonomics and sensor integration in public transportation system design for improving commuter comfort and safety in highly congested urban transport systems. Future researches are also discussed.